2015
DOI: 10.1088/0960-1317/25/12/125008
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in energy harvesting capabilities by using different shapes of piezoelectric bimorphs

Abstract: The small amount of power needed by microelectronic devices opens up the possibility to convert part of the vibration energy present in the environment into electrical energy, using several methods. One such method is to use piezoelectric material as an additional layer in cantilever beams to harvest vibration energy for self-powered sensors. The geometry of a piezoelectric cantilever beam will greatly affect its vibration energy harvesting ability. Tapering and changing the configuration as ways to increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…It is shown that increasing the width W 2 (at free end) lowers the resonance frequency, which agrees with our results. It was also shown that the trapezoidal shape generates higher voltage compared to the simple rectangular cantilever beam bimorph which matches our findings in previous works [6,12]. In this paper, we explore a unique design of 2-piece trapezoidal shaped piezoelectric bimorph to understand its effects on harvested power, power density, and bandwidth.…”
Section: Introductionsupporting
confidence: 88%
“…It is shown that increasing the width W 2 (at free end) lowers the resonance frequency, which agrees with our results. It was also shown that the trapezoidal shape generates higher voltage compared to the simple rectangular cantilever beam bimorph which matches our findings in previous works [6,12]. In this paper, we explore a unique design of 2-piece trapezoidal shaped piezoelectric bimorph to understand its effects on harvested power, power density, and bandwidth.…”
Section: Introductionsupporting
confidence: 88%
“…Apart from the tuning of the material composition, the rest of the piezoelectric energy harvesting research has focused on the structural design and optimization for different applications. The most popular structures used in piezoelectric energy harvesters include cantilever, stack cymbal configuration, diaphragm configuration, and shear mode configuration . The cantilever structure is suitable for low input force, small acceleration, and mid‐high frequencies (tens of Hz or above), but it allows large amplitude/deformation.…”
Section: Development Of Single‐source Energy Harvestersmentioning
confidence: 99%
“…It can be found numerous reports on investigations related to optimization and application of different shapes and vibration modes of piezoelectric cantilevers which can be used for energy harvesting (Thein and et al 2016;Hosseini and Hamedi, 2015;Mohamed and et al 2016;Žižys and et al 2015;Ostaševičius and et al 2015). Moreover, numerous models were developed in order to predict mechanical and electrical characteristics of cantilevers with different shapes Erturk and Inman, 2009;Deitl and et al 2010).…”
Section: Cantilever Based Piezoelectric Energy Harvestersmentioning
confidence: 99%